Companies and climate change : theory and law in the United Kingdom / Lisa Benjamin, Lewis & Clark College. - Benjamin, Lisa (Writer of Companies and climate change) (Cambridge studies on environment, energy, and natural resources governancee., 2021)
Companies lie at the heart of the climate crisis and are both culpable for, and vulnerable to, its impacts. Rising social and investor concern about the escalating risks of climate change are changing public and investor expectations of businesses and, as a result, corporate approaches to climate change. Dominant corporate norms that put shareholders (and their wealth maximization) at the heart of company law are viewed by many as outdated and in need of reform. Companies and Climate Change analyzes these developments by assessing the regulation and pressures that impact energy companies in the UK, with lessons that apply worldwide. In this work, Lisa Benjamin shows how the Paris Agreement, climate and energy law in the EU and the UK, and transnational human rights and climate litigation, are regulatory and normative developments that illustrate how company law can and should act as a bridge to progressive corporate climate action.